Effect of the Mediterranean diet on blood pressure in adults with and without hypertension: a systematic review and meta-analysis of randomized controlled trials. (14th October 2021) - Filippou, C; Thomopoulos, C; Kouremeti, M; Sotiropoulou, L; Nihoyannopoulos, P; Tousoulis, D; Tsioufis, K
Abstract: Background: It is unclear whether the Mediterranean diet (MedDiet) has a favorable effect on blood pressure (BP) levels because among randomized controlled trials (RCTs) investigating the MedDiet-mediated BP reduction there are significant methodological and clinical differences. Purpose: The purpose of this study was to comprehensively assess the MedDiet BP-effect compared to the usual diet or another dietary intervention (e.g. low-fat diet) in adults with and without hypertension, accounting for different confounders. Methods: We systematically searched Medline and the Cochrane Collaboration Library databases and identified 35 RCTs (13, 943 participants). Random-effects model was used to calculate the mean attained systolic BP (SBP) and diastolic BP (DBP) differences during follow-up. Subgroup and meta-regression analyses were also conducted. Results: Compared to the usual diet and all other active intervention diets the MedDiet reduced SBP and DBP (difference in means: −1.5 mm Hg; 95% CI: −2.8, −0.1; P=0.035, and −0.9 mm Hg; 95% CI: −1.5, −0.3; P=0.002, respectively). Compared only to the usual diet the MedDiet reduced SBP and DBP, while compared to all other active intervention diets or only to the low-fat diet the MedDiet did not reduce SBP and DBP. The MedDiet reduced DBP levels to a higher extent in trials with a mean baseline SBP ≥130 mm Hg, while both SBP and DBP were reduced more in trials with a mean follow-up period ≥16 weeks. The quality of evidence was rated as moderate for both outcomes according to the grading of recommendations, assessment, development and evaluation (GRADE) approach. Conclusions: The adoption of the MedDiet was accompanied by a relatively small, but yet significant BP reduction, while higher baseline SBP levels and longer follow-up duration enhanced the BP-lowering effect of the intervention FUNDunding Acknowledgement: Type of funding sources: None.